Left atrial appendage closure with zero fluoroscopic exposure via intracardiac echocardiographic guidance. (25th November 2020) - Du, X.F; Chu, H.M; Shen, C.J; He, B
Abstract: Background: Percutaneous left atrial appendage closure (LAAC) is currently guided by fluoroscopy and transesophageal echocardiography (TEE). Objective: We report an LAAC technique using intracardiac echocardiography (ICE) and electroanatomic mapping system (EAMS) under local anesthesia without fluoroscopy exposure. Methods: Seven non-valvular atrial fibrillation (NVAF) patients with high risk of stroke and bleeding (male 5/7, aged 71.7±8.8 years, mean CHA2DS2-VASc score 5.1±2.1; mean HAS-BLED score 3.0±1.2) were enrolled. ICE probe was advanced into left atrium (LA) navigated by the EAMS. LAA sizing and LAmbreTM device implantation were guided by ICE following the orthogonal tri-axial algorithm (Axis-X: from left pulmonary veins [LPVs] to LAA; Axis-Y: from right PV ostium to LAA; Axis-Z: from lower LA to LAA). Results: There were two cauliflower-like, two chicken-wing-like and three cactus-like LAAs. The mean diameters of ostia and landing zone were 21.4±3.9mm and 20.4±4.2mm, respectively. LAmbre devices with a mean umbrella diameter of 23.7±4.2mm and cover disc diameter of 29.4±3.6mm were successfully implanted and acute complete LAA sealing without peri-device leak (PDL) were achieved in all cases. The mean procedural duration was 73.0±21.4min. No fluoroscopy exposure nor contrast consumption were recorded. No procedure-related complications were documented. The PDL at 45-day follow-up was 1.7±0.8mm. No stroke or thromboembolic events were documented. Conclusions: The fluoroscopic exposure could be minimized, even to zero, in the ICE-guided LAAC procedures feasibly and safely using LAmbre devices. The orthogonal tri-axial assessment is considered efficacious and safe for the procedures. Funding Acknowledgement: Type of funding source: None